A Comparative Study on E-Learning Implementation in Higher Education In Response to The Covid-19 Pandemic - Paula Dewanti; Ni Putu Linda Santiari; Kadek Vishnu Vedamurthi (Universitas Muhammadiyah Kalimantan Timur, 2022)
The aim of this study was to explore the use of distance learning in Indonesian universities during the pandemic. This was a continuation of previous research on the implementation of Digital Learning in several countries as an Emergency Response to the COVID-19 Pandemic. Given the uncertainty surrounding the end of the pandemic, as well as government regulations expanding the use of distance learning, researchers believe it is crucial to examine student attitudes toward implementation. In this study, the comparative study method was used to compare the similarities and differences between two or more properties and facts of the object under study based on a particular frame of mind. The findings indicate that there are similarities in the implementation of distance learning, which involves transforming face-to-face sessions in a classroom setting into live face-to-face sessions in virtual classrooms. The initiatives of each university are in line with government recommendations. The implementation, however, varies slightly due to differences in characteristics such as facility and infrastructure readiness that exist on each of these campuses. Further research focusing on Student Engagement and Student Experience, using larger data sets, would be expected to provide much more value and best practices for E-Learning implementation during the current COVID-19 pandemic.